Analisis Ragam Bahasa Guru dan Siswa dalam Interaksi Kelas di SDN 1 Kabunderan - Rizqina, Adina Anisnaeni; Saddhono, Kundharu; Suhita, Raheni (Research in Education and Technology (REGY), 2023)
This The research entitled "Analysis of Teacher and Student Language Variety in Class Interaction at SDN 1 Kabunderan" aims to describe the use of various languages ​​of teachers and students in the school environment of SDN 1 Kabunderan. This research method uses a qualitative descriptive method based on existing facts. Data obtained based on observations in the field. The results of research conducted at SDN 1 Kabunderan show that there are a variety of standard, official, relaxed, and familiar languages ​​used by teachers and students such as the use of mixed languages ​​of Indonesian, Javanese and English. The most dominant use of mixed languages ​​is the variety of Indonesian with Javanese ngapak, while the non-dominant use is found in the variety of Indonesian and English. The occurrence of various languages ​​is motivated by Javanese cultural factors, foreign languages, technological developments, social media developments, familiarity, and mutual respect.